Inhibition of PKA/CREB1 pathway confers sensitivity to ferroptosis in non-small cell lung cancer - Guangyao Shan; Guoshu Bi; Guangyin Zhao; Jiaqi Liang; Yunyi Bian; Huan Zhang; Xing Jin; Zhengyang Hu; Guangyu Yao; Hong Fan; Cheng Zhan (Respiratory Research, 2023)
Abstract Ferroptosis is a type of regulated cell death characterized by iron accumulation and lipid peroxidation. The molecular mechanisms underlying ferroptosis regulation in non-small cell lung cancer (NSCLC) are poorly understood. In this study, we found that protein kinase A (PKA) inhibition enhanced ferroptosis susceptibility in NSCLC cells, as evidenced by reduced cell viability and increased lipid peroxidation. We further identified cAMP-responsive element protein 1 (CREB1), a transcription factor and a substrate of PKA, as a key regulator of ferroptosis. Knockdown of CREB1 sensitized NSCLC cells to ferroptosis inducers (FINs) and abolished the effects of PKA inhibitor and agonist, revealing the pivotal role of CREB1 in ferroptosis regulation. Using a high-throughput screening approach and subsequent validation by chromatin immunoprecipitation (ChIP) and dual-luciferase assays, we discovered that CREB1 transcriptionally activated stearoyl-CoA desaturase (SCD), an enzyme that catalyzes the conversion of saturated fatty acids to monounsaturated fatty acids. SCD conferred ferroptosis resistance by decreasing the availability of polyunsaturated fatty acids for lipid peroxidation, and its overexpression rescued the effect of CREB1 knockdown on ferroptosis in vitro. Besides, CREB1 knockdown suppressed xenograft tumor growth in the presence of Imidazole Ketone Erastin (IKE), a potent FIN, and this effect was reversed by SCD. Finally, we showed that high expression of CREB1 was associated with poor prognosis in NSCLC patients from public datasets and our institution. Collectively, this study illustrates the effect of PKA/CREB1/SCD axis in regulating ferroptosis of NSCLC, targeting this pathway may provide new strategies for treating NSCLC patients.